Feature of growing of winter crops at the terms of changes of climate - О. І. Рудник-Іващенко (Plant Varieties Studying and Protection)
Discussed problems of planetary changes of climate, through that it is necessary to revise the terms of sowing of winter crops, and also structure of sowing of agricultural cultures. The brought transpiration coefficients over of basic agricultural cultures, that must be taken into account for forming of structure of their sowing. On the example of wheat winter-annual the done attempt to be determined with priority directions in the selection of agricultural cultures.